Different metal–ligand ratios regulated two Cd(II)-containing viologen-derived photochromic coordination polymers. (April 2022) - Li, Zhao-Hao; Xue, Li-Ping; Li, Shuo; Zang, Ping-Fang
Abstract: Through meticulous tuning of the metal-ligand ratios, two new coordination polymers (CPs) based on N -(3-carboxypyridin-5-yl)-4, 4′-bipyridinium (cpbpy) and 2, 5-thiophenedicarboxylic acid (H2 L) mixed ligands, namely, [Cd(cpbpy)(L)(H2 O)2 ](H2 O)3 n (1 ) and [Cd2 (cpbpy)(L)2 (H2 O)4 ](H2 O)4 n (2 ) have been successfully synthesized. The single-crystal X-ray diffraction analysis reveal compounds 1 and 2 both crystallize in triclinic P -1 space group, while compound 1 is a 1D chain structure and compound 2 displays a 2D layered structure with 3-connected 6 3 -hcb topology. 1 and 2 exhibit photochromism and undergo distinct color changes from light yellow to green due to the formation of radicals. This work provides a simple method via regulation of metal–ligand ratios to synthesize new photochromic CPs. Graphical abstract: Image 1 Highlights: Two Cd(II) coordination polymers have been synthesized via regulation of metal–ligand ratios. One compound is a 1D chain structure, and the other compound is a 2D layered structure with 3-connected 6 3 -hcb topology. Compounds exhibit sensitively photochromic behavior.